2011
DOI: 10.1002/ajmg.a.33878
|View full text |Cite
|
Sign up to set email alerts
|

11p14.1 microdeletions associated with ADHD, autism, developmental delay, and obesity

Abstract: Genomic copy number imbalances are being increasingly identified as an important cause of intellectual disability and behavioral abnormalities. The typical deletion in WAGR syndrome encompasses the PAX6 and WT1 genes, but larger deletions have been associated with neurobehavioral abnormalities and obesity. We identified four patients with overlapping interstitial deletions on 11p14.1 and extending telomeric to the WAGR critical domain. The minimal overlapping critical chromosomal region was 2.3 Mb at 11p14.1. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
57
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 47 publications
3
57
0
1
Order By: Relevance
“…Moreover, underlying the key role of the LIN7:IRSp53 association in neuritogenesis, our results suggest that neurodevelopmental disorders, such as human attentiondeficit/hyperactivity disorder (ADHD), recently associated with polymorphisms of LIN7 or IRSp53 or altered expression of LIN7 in humans (Lanktree et al, 2008;Ribasés et al, 2009;Zucker et al, 2010;Shinawi et al, 2011) may be due to unbalanced alterations in the expression of LIN7 and/or IRSp53 or to mutations that prevent their interaction.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Moreover, underlying the key role of the LIN7:IRSp53 association in neuritogenesis, our results suggest that neurodevelopmental disorders, such as human attentiondeficit/hyperactivity disorder (ADHD), recently associated with polymorphisms of LIN7 or IRSp53 or altered expression of LIN7 in humans (Lanktree et al, 2008;Ribasés et al, 2009;Zucker et al, 2010;Shinawi et al, 2011) may be due to unbalanced alterations in the expression of LIN7 and/or IRSp53 or to mutations that prevent their interaction.…”
Section: Discussionmentioning
confidence: 80%
“…In vertebrates, there are three genes, LIN7-A-B-C also named MALS/Veli-1-2-3, and alterations in these genes cause renal defects and synaptic dysfunctions (Olsen et al, 2007), and mice harbouring null mutations of all the three LIN7 isoforms die perinatally with respiratory problems and impaired synaptic transmission (Olsen et al, 2005). Moreover, polymorphisms and altered expression of LIN7 have been recently associated with human psychiatric conditions such as attention-deficit/ hyperactivity disorder (ADHD) and neurodegenerative diseases (Lanktree et al, 2008;Zucker et al, 2010;Shinawi et al, 2011). Interestingly, certain IRSp53 alleles in humans have also been linked to ADHD (Ribasés et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…al., 2010; Wentzel et al, 2010;Dasouki et al, 2011;Shinawi et al, 2011;Vergult et al, 2012;D'Angelo et al, 2013;Doco-Fenzy et al, 2014;Vuillaume et al, 2014].…”
unclassified
“…Recent studies reported that deletion of BDNF (brain-derived neurotrophic factor), which is present in 11p14.1, is attributable to the obesity found in WAGR syndrome (2). 11p14.1 microdeletions are associated with attention-deficit hyperactivity disorder, autism, developmental delay, and obesity in humans (10). PRRG4 (transmembrane ␥-carboxyglutamic acid protein 4) and SLC1A2 (solute carrier family 1 member 2), which have been reported to be deleted in some WAGR syndrome patients, may be implicated in autism (4).…”
mentioning
confidence: 99%